2006
DOI: 10.1101/lm.351706
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent glutamate induction of synaptic plasticity in cultured hippocampal neurons

Abstract: A common denominator for the induction of morphological and functional plasticity in cultured hippocampal neurons involves the activation of excitatory synapses. We now demonstrate massive morphological plasticity in mature cultured hippocampal neurons caused by a brief exposure to glutamate. This plasticity involves a slow, 70%-80% increase in spine cross-section area associated with a significant reduction in the width of dendrites. These changes are age dependent and expressed only in cells >18 d in vitro (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…[77][78][79][80][81][82][83][84][85][86] Excessive activation of glutamate receptors has been shown to result in excitotoxicity with irreversible disruption of ion homeostasis and cell death. 87 This is in line with many studies reporting that excitotoxic mechanisms contribute to alterations in neuroplasticity 88 and memory. 89 Thus, our results may suggest that homeostatic mechanisms that keep cortical excitability within a normal physiological range are impaired in CI.…”
Section: Discussionsupporting
confidence: 83%
“…[77][78][79][80][81][82][83][84][85][86] Excessive activation of glutamate receptors has been shown to result in excitotoxicity with irreversible disruption of ion homeostasis and cell death. 87 This is in line with many studies reporting that excitotoxic mechanisms contribute to alterations in neuroplasticity 88 and memory. 89 Thus, our results may suggest that homeostatic mechanisms that keep cortical excitability within a normal physiological range are impaired in CI.…”
Section: Discussionsupporting
confidence: 83%
“…The mechanism of this progressive decline cannot be fully explained with our data, as there are a number of biologic and environmental changes associated with age including decreasing synaptic plasticity and cortical volume with increasing age. [41][42][43] A greater degree of disability 5 years postinjury among older patients may be explained by an increased number of actual and perceived health problems as compared to younger patients. A recent investigation noted patients older than 55 years of age report more problems with headaches, body temperature changes, communication difficulties, sleeping problems, and back and neck pains than age matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…The initial expansion was dependent on activation of NMDA receptors in the spine head while a long-lasting expansion was dependent on activation of kinases (566). Later studies reported that the change in spine volume was smaller than in the original report [Yang et al,40% (566); Lai et al, 40% (267)] and may develop over a longer time period [20 min (267, 583) or longer (442)]. Regardless of the magnitude of the immediate effects, the ability of spines to change their volume over a short time is impressive indeed.…”
Section: B Spine Expansionmentioning
confidence: 92%